Pengaruh Motivasi Belajar dan Lingkungan Teman Sebaya terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi - Azie Nurnazathul; Oknaryana Oknaryana (Jurnal Ecogen, 2021)
This type of research is descriptive associative. The population in this study were all 96 students majoring in social studies at SMA Negeri 1 Lengayang. Sampling technique with a total sampling with a sample of 96 people. Data analysis techniques: descriptive analysis and inductive analysis of multiple analysis requirements test, namely: normality test, homogeneity test and multicollinearity test. This study aims to analyze the effect of learning motivation on student learning outcomes in the economics subject of class XI IPS SMA Negeri 1 Lengayang, the influence of peer environment on economic learning outcomes economics subjects in class XI IPS SMA Negeri 1 Lengayang, and the influence of learning motivation and the environment. peers on Student Learning Outcomes in Economics Subject Class XI IPS SMA Negeri 1 Lengayang. The results showed that (1) there was a positive and significant influence between learning motivation on economic learning outcomes for students of class XI IPS SMA Negeri 1 Lengayang, (2) there was a positive and significant influence between peer environment on student learning outcomes. on the Economics subject of class XI IPS SMA Negeri 1 Lengayang, (3) there is a positive and significant influence between learning motivation and peer environment on student learning outcomes in the subject of Economics class XI IPS SMA Negeri 1 Lengayang